2016
DOI: 10.4081/monaldi.2009.370
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of complications in bronchoscopy. Multicentre prospective study of 20,986 bronchoscopies

Abstract: This study has shown that bronchoscopy is a safe method with low incidence of mortality and complications. The preparation, experience and continuous training of the operators of the medical and nursing team seem to play a fundamental role in reducing the incidence of complications at least in certain procedures such as BB and TBB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 26 publications
6
109
1
2
Order By: Relevance
“…Studies from the 2000s [4,5] have reported complication rates of 1.08−6.6% and mortality rates of 0.02−0.045%. A large survey in Japan [2] found complication rates ranging from 0.15 to 2.06% and a mortality rate of 0.004%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from the 2000s [4,5] have reported complication rates of 1.08−6.6% and mortality rates of 0.02−0.045%. A large survey in Japan [2] found complication rates ranging from 0.15 to 2.06% and a mortality rate of 0.004%.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, it was caused by brushing of a solitary lesion in a patient with suppurative pneumonia, other deaths were attributed to cerebral infarction caused by air emboli following forceps biopsy of a solitary lesion, aortic dissection following simple bronchoscopy for diffuse lesions, and acute exacerbation of interstitial pneumonia after endobronchial ultrasonography transbronchial needle aspiration of hilar lymph node. Since hemostasis techniques have been improving based on a great deal of experience, fatal case of hemorrhage due to TBLB have not been reported in recent years [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events are rare but include: bleeding (0.12%), hypoxia, loss of airway, pneumothorax (0.1-0.16%), or mortality (0-0.02%) (10)(11)(12).…”
Section: Flexible Bronchoscopymentioning
confidence: 99%
“…Diagnostic sampling may lead to immediate, although rare, complications, such as intrabronchial bleeding, bronchospasm, hypoxemia, hemodynamic variations and pneumothorax (1,5,6).…”
mentioning
confidence: 99%
“…We know from the literature that significant fall in Forced Expiratory Volume in 1 second (FEV 1 ), and forced vital capacity (FVC) occurs after endoscopic procedure, during both routine bronchoscopy and procedures, which include bronchoalveolar lavage (BAL) and biopsy (6). This impairment of the lung function reflects the gas exchange efficiency, with a reduction of the PaO 2 (7).…”
mentioning
confidence: 99%